Linear Investigation on Tapered Steel Isolated Plates with Zigzag Corrugated Web - Omnia Kharoob; Ahmed El Hadidy; Saba Hammad (Journal of Engineering Research - Egypt, 2023)
Owing to the benefits of corrugated steel webs, they are frequently utilized in a variety of buildings, particularly bridges. They have good and beautiful appearance, Secondly, they exhibit large out of plane stiffness so they have a high ability to resist shear buckling which is known as accordion effect. There are many profiles of corrugation such as trapezoidal,curved and zigzag shapes, many researches studied the trapezoidal profile as prismatic and tapered but zigzag profile was studied as a prismatic only, So It was focused in this research to examine the behavior of the elastic buckling stress τ_cr on tapered corrugated webs with zigzag profile for case Ι exposed to shear load. The ABAQUS Program is utilized here to make a series of finite element (FE) simulations to investigate the factors which affect the behavior of the elastic buckling stress and to modify the equation of τ_(cr,T) to be suitable for zigzag profile.